Semantic Function of Horticulture Terms in English and Uzbek Languages (Eurasian Research Bulletin, 2023)
This article devoted to study of horticultural terms and their definitions. We showed why we needed to study the horicultural terms by comparing them in the English and Uzbek languages. There are some researches on the comparative analysis of the terms in Modern English and other languages, so our research is the one of them which is devoted to comparative analysis of the horicultural terms in Modern English and Uzbek and about the methods of teaching agricultural terms at Uzbek.